2020
DOI: 10.36937/cebel.2020.004.005
|View full text |Cite
|
Sign up to set email alerts
|

Improve Geotechnical Properties of Soils Using Industrial Wastes: A Review

Abstract: The engineering problems of problematic soils are mainly related to their mechanical, physical, and mineralogical properties. Extensive efforts have been directed to mitigate damages that may happen for structures constructed on, or in these soils' types. Both conventional materials (e.g. cement, lime, etc.), chemical and produced materials were blended, mixed, or added to soils to improve their geotechnical properties. In the last years, different additives from the wastes of industrial processes have been ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The process of fluctuation in groundwater levels in the region is affected by the increase and decrease in the water levels in Al-Warrar canal, in addition to the amount of rain falling in the region with the increase and decrease the amount of water coming from the aquifers surrounding the study area as shown in Figure (2). Therefore two possibilities were taken for the movement and transmission of groundwater, one of which is the movement of groundwater from the study area to Al Warrar Canal and the other is groundwater movement from the canal to the study area depending on the increase and decrease in the water level of Al Warrar Canal.…”
Section: Groundwater Levels Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of fluctuation in groundwater levels in the region is affected by the increase and decrease in the water levels in Al-Warrar canal, in addition to the amount of rain falling in the region with the increase and decrease the amount of water coming from the aquifers surrounding the study area as shown in Figure (2). Therefore two possibilities were taken for the movement and transmission of groundwater, one of which is the movement of groundwater from the study area to Al Warrar Canal and the other is groundwater movement from the canal to the study area depending on the increase and decrease in the water level of Al Warrar Canal.…”
Section: Groundwater Levels Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to determine groundwater levels, especially in the layers those close to the ground surface to know the properties of soils and the effect of the groundwater on it before creating for any construction or service project. [2], showed that, field and laboratory tests were carried for three great water projects in Basra. Thirty-nine boreholes were drilled at a depth of 30 m. The results were observed the soil of Basra forms mainly sand, clay, silt, clayey silt, and silty clay, with plasticity low for this soil.…”
Section: Introductionmentioning
confidence: 99%
“…Although landfilling is a common method of disposing of fly ash, rising disposal costs and significant environmental concerns regarding the leaching of latent toxic substances from the ash to soil, surface water, and groundwater [114][115][116] make the utilization of fly ash a more appealing alternative to direct landfilling [117]. Industrial waste is frequently utilized as a stabilizer to lessen the negative effects on engineering properties of weak soils through reactions with soil particles that improve the engineering qualities of the soils [118]. Accordingly, fly ash behavior was covered by previous research.…”
Section: Fly Ashmentioning
confidence: 99%
“…A number of these materials are unavailable in some regions, while others are impractical for local-building reasons [19][20]. The potency of recycling and/or reusing byproduct waste in engineering construction has recently attracted the attention of many researchers; doing so would reduce the environmental issues related to waste disposal and the costs of materials [21][22][23][24][25][26][27][28][29]. There is a kind of industrial waste called cement kiln dust (CKD), created when exhaust gases from a cement kiln.…”
Section: Introductionmentioning
confidence: 99%